Studi Literatur Pemanfaatan Kulit Buah Genus Citrus sebagai Larvasida Aedes aegypti - Niken Suci Meliani Hernawan; Sri Peni Fitrianingsih; Fetri Lestari (Bandung Conference Series: Pharmacy, 2022)
Abstract. One of the ways to control the main vector of DHF, Aedes aegypti mosquito, is by using larvicides. The use of natural larvicides is an alternative in overcoming the negative impacts of using chemical larvicides. The Citrus genus is one of the plant that can be used as natural larvicides. In addition, the Citrus genus industry produces large amounts of waste or by-products such as peels, seeds and pulp, which represent 50 % of the weight of fresh fruit, so that the use of fruit peels can be one way to treat waste. The aim of the study was to determine the larvicidal potential of fruit peels of the genus Citrus against the Aedes aegypti mosquito and the compounds that play a role in the larvicidal activity. The study was performed by systematic literature review using selected articles from reputable database that meet the inclusion and exclusion criteria. The results showed that 6 plant species from the genus Citrus had larvicidal activity against Aedes aegypti consisting of Citrus sinensis, Citrus limetta, Citrus reticulata, Citrus paradisi, Citrus aurantifolia, dan Citrus limettioides. From various studies, the essential oil microemulsion and the inclusion complex of β-cyclodextrin essential oil C. sinensis, and C. limettioides essential oil are included in the classification of active larvicides (LC50 < 50 ppm). Compounds that are believed to have a role in the larvicidal activity of Citrus fruit peels include limonene and γ-terpinen . Abstrak. Salah satu cara pengendalian vektor utama penyakit DBD yaitu nyamuk Aedes aegypti ialah dengan larvasida. Penggunaan larvasida alami menjadi salah satu alternatif dalam mengatasi dampak negatif dari penggunaan larvasdia kimia. Genus Citrus menjadi salah satu genus tanaman yang dapat dimanfaatkan sebagai larvasida alami. Disamping itu industri genus Citrus menghasilkan limbah atau produk sampingan yang cukup besar seperti kulit biji serta ampasnya yang mewakili 50 % dari berat buah segar, sehingga pemanfaatan kulit buahnya dapat menjadi salah satu cara untuk mengolah limbah. Penelitian ini bertujuan untuk mengetahui potensi larvasida dari kulit buah genus Citrus terhadap nyamuk Aedes aegypti dan senyawa yang berperan dalam aktivitas larvasida tersebut. Metode penelitian dilakukan dengan studi literatur terhadap sejumlah artikel dari database bereputasi yang memenuhi kriteria inklusi dan eklusi. Hasil penelitian menunjukkan 6 spesies tanaman dari genus Citrus memiliki aktivitas larvasida terhadap Aedes aegypti yang terdiri dari Citrus sinensis, Citrus limetta, Citrus reticulata, Citrus paradisi, Citrus aurantifolia, dan Citrus limettioides. Dari berbagai penelitian mikroemulsi dan kompleksi -siklodekstrin minyak atsiri C. sinensis serta minyak atsiri C. limettioides termasuk dalam klasifikasi larvasida aktif (LC50 < 50 ppm). Senyawa yang diyakini memiliki peran dalam aktivitas larvasida kulit buah Citrus diantaranya ialah limonen dan -terpinen.